The Effectiveness of Surgical Appendectomy in Curing the Right Lower Quadrant Abdomen Pain - Mohanty, Aalok (Advanced Concepts in Medicine and Medical Research Vol. 8, 2023)
This chapter aims to investigate the role of Surgical Appendectomy to treat the chronic pain in the right lower quadrant with the selected case. Chronic right-lower-quadrant abdominal pain is very common among growing population. This observational experiment was done in Mahatma Gandhi Medical College and Research Institute with 212 selected cases. The selected year for the observational study was in between January 2014 and August 2015. The patients with clinical diagnosis of chronic RLQ pain and undergoing appendicectomy were exposed in this study. Statistical analysis of the observation was carried out using SPSS version 19.0 (IBM SPSS, US) software with Regression Modules. Descriptive analyses were reported as mean and standard deviation of continuous variables. Paired t test and independent t test were used to analyze the data. As per the findings, out of 212 cases studied, the maximum numbers of patients were in the age group 31-40 years (24.52%). Additionally, in that study total of 35 cases with clinically evaluated appendicitis (17 cases) and cases with pain persisting or recurring in right lower abdomen (18 cases) over a period of 6 weeks or more were assessed. Moreover, seventeen (94.44%) patients from right lower abdomen pain group had pain relief after appendicectomy. Of 82 (100%) patients who underwent appendicectomy, around 79 cases (96.34%) of the selected individuals were completely pain free, and only 3 (3.66%) cases have not experienced any improvement after elective appendicectomy. There was no mortality. Out of 82 patients, 52 (63.41%) patients had pathological signs of appendicitis and 30 (36.59 %) patients showed the normal appendix.